Harnessing the Potential of Wheat-Pea Species Mixtures: Evaluation of Multifunctional Performance and Wheat Diversity - Timaeus, Johannes; Weedon, Odette Denise; Finckh, Maria Renate (Frontiers in Plant Science, 2022)
Species mixtures and heterogeneous crop populations are two promising approaches for diversified ecological cropping systems with increased resilience and reduced dependency on external inputs. Inter- and intraspecific diversity were evaluated in combination using 15 wheat entries including line cultivars and heterogeneous populations (HP) from central Europe and Hungary and one winter pea cultivar under organic conditions. Monocultures and wheat-mixtures were evaluated multifunctionally for yield, quality, land use efficiency, crop protection and wheat entry traits. Mixtures increased cereal grain quality, weed suppression, resource use efficiency, yield gain and reduced lodging. Effects were stronger in 2018/19, characterized by dry and nutrient poor conditions than in 2019/20 when nutrient levels were higher. Wheat entries varied considerably for protein content and yield in both mixtures and monocultures. Under higher nutrient availability, entry-based variation was reduced in both systems and peas were suppressed. Due to low disease pressure wheat entries varied little in disease protection services and mixture effects on disease were low. The multicriteria framework identified stability of yields, yield gains and quality under high environmental variability of mixtures as clear agronomic advantages with HPs being considerably more stable than line cultivars. Some line cultivars outperformed heterogeneous populations for either protein content or yield across environments but not both simultaneously. Trait analysis revealed a possible link between harvest index and competitive ability, which can increase yield performance in specific line cultivars but less so in HPs. System cultivar interactions were generally very low but were highly dependent on the environmental conditions. We conclude that, while cultivar breeding for mixtures can be successful in monocultures, high environmental variation highlights the necessity of evaluating cultivars in mixtures. In addition, the use of intraspecific diversity within interspecific systems can be a valuable addition to further improve mixture performance and its stability under increasing environmental stresses due to climate change.